If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = 5(3x + -2) Reorder the terms: 3(-2 + x) = 5(3x + -2) (-2 * 3 + x * 3) = 5(3x + -2) (-6 + 3x) = 5(3x + -2) Reorder the terms: -6 + 3x = 5(-2 + 3x) -6 + 3x = (-2 * 5 + 3x * 5) -6 + 3x = (-10 + 15x) Solving -6 + 3x = -10 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -6 + 3x + -15x = -10 + 15x + -15x Combine like terms: 3x + -15x = -12x -6 + -12x = -10 + 15x + -15x Combine like terms: 15x + -15x = 0 -6 + -12x = -10 + 0 -6 + -12x = -10 Add '6' to each side of the equation. -6 + 6 + -12x = -10 + 6 Combine like terms: -6 + 6 = 0 0 + -12x = -10 + 6 -12x = -10 + 6 Combine like terms: -10 + 6 = -4 -12x = -4 Divide each side by '-12'. x = 0.3333333333 Simplifying x = 0.3333333333
| 3x+1=9-5x | | 3w+36=4w-18 | | 3(k+7)=75 | | x^5+2x^2=0 | | 5a+2(3a+4)-2a= | | 2b^2-3b=5 | | N=55000-2000x | | 7v-5=4v+4 | | 3(v+4)+v=20 | | 5x-5+6-3x=0 | | q*4q*5q= | | 5(2y+10)=110 | | 3x+2y-z=23 | | 3-5x=4+2x | | X^4-3x^2-x^3+4x-4=0 | | x=6.25+0.25y+-0.5z | | 5(x+6)+2=37 | | 3(x+1)-x+4=2x+8 | | 282-10x=20x+12 | | z^3-i*z^2+4z-4i=0 | | x^4-7x^3+7x^2+42x+63=0 | | 4(x+12)+2(x+18)=-6 | | x^4+11x^3+7x^2+42x+63=0 | | x^4+6x^3+7x^2+42x+63=0 | | (5-x)*(6x+2)+5=0 | | 2*x^2+4=0 | | 4(x+2)-3(x+1)=3 | | (5-x)*(6x+2)=5 | | x^4+6x^3-7x^2-42x-63=0 | | 2(3x-1)-4(2x+5)=-5 | | 7x-5=2b+15 | | 3x+2y-z=28 |